PENGARUH KOMUNIKASI, KERJASAMA TIM, KEPEMIMPINAN DAN PENGAMBILAN KEPUTUSAN KEPALA SEKOLAH TERHADAP KINERJA GURU PADA SEKOLAH DASAR NEGERI DALAM KECAMATAN PEUSANGAN KABUPATEN BIREUEN - Win, Sudirman; Fauzi (LPPM-UNIKI, 2022)
The purpose of this study on elementary school teachers in Peusangan District, Bireun Regency, was to find out: the influence of communication, teamwork, leadership and principal's decision-making on the performance of elementary school teachers in Peusangan District, District Bireuen. This research is in the form of a survey with a questionnaire instrument and analytical method using path analysis and data processing with SPSS v.20. The results showed that, 1) There was an influence of aspects of teacher communication in schools on teacher performance, which was very significant at 30.19%, 2) There was a positive and significant influence on teacher Teamwork on teacher performance by 11.72%, 3) It was proven that there was an effect Leadership. The principal on the performance of elementary school teachers is 10.94%, 4) and the influence of Principal Decision Making on teacher performance is very significant at 8.21%. and 5). Simultaneously, the influence of communication, teamwork, leadership and decision-making principals on the performance of elementary school teachers in Peusangan District, Bireuen Regency is 62%. While the remaining 38% of the variables not examined, such as teacher competence, work facilities, organizational climate, education, and others